(untitled) (Journal of the College of Education for Women, 2019)
The research aims at identifying The Effect of Woods model in the Acquisition of Grammatical Concepts on students at the Sixth Primary. The total number of students is (49) male and female. students are distributed in two groups . The First group is the experimental group which is taught the( Woods Model) and it is (25) students . The second group is the control group which is taught according to the traditional method of teaching and it is (24) students . The researcher has matched between the two groups by the following variables : the age (in months), their intelligence, their parents, academic level of education . The research has constructed multiple choice test of (20) items . The reliability of The test has been calculated and it is (0,80). After processing The results statistically, T - Test , has shown that there is a statistically significant difference infavour to the experimental group.